CORRELATION BETWEEN MRI-BASED BRAIN VOLUME CHANGES AND COGNITIVE DECLINE IN PATIENTS WITH MILD COGNITIVE IMPAIRMENT: A PROSPECTIVE OBSERVATIONAL STUDY. - Surpam, Karishma Khushalrao (Student’s Journal of Health Research Africa, 2025)
Background Mild Cognitive Impairment (MCI) is an intermediate stage between normal cognitive aging and dementia, characterized by subtle cognitive decline. MRI-based brain volumetry, particularly of the hippocampus and entorhinal cortex, has been proposed as a potential biomarker for predicting cognitive deterioration. This study aimed to assess the relationship between structural brain volume changes and cognitive decline among patients diagnosed with Mild Cognitive Impairment (MCI). Methods A prospective cohort of 100 patients diagnosed with MCI (mean age 68.5 ± 6.7 years; 54% male) was enrolled. Baseline cognitive function was assessed using the Mini-Mental State Examination (MMSE), and MRI-based volumetric analysis of the hippocampus and entorhinal cortex was conducted. Participants were followed for 12 months, with cognitive status reassessed. Pearson correlation and multiple linear regression analyses were performed to examine associations between brain volume and cognitive performance. Results Baseline MMSE scores averaged 26.2 ± 1.8. Pearson correlation revealed a significant positive association between hippocampal volume (r = 0.58, p < 0.001) and entorhinal cortex volume (r = 0.51, p < 0.001) with MMSE scores. Participants with cognitive decline (n = 40) exhibited significantly greater hippocampal volume reduction (5.2% ± 1.1%) compared to stable participants (2.1% ± 0.9%; p < 0.001). Multiple regression analysis identified hippocampal (β = 0.43, p < 0.001) and entorhinal cortex volumes (β = 0.37, p = 0.002) as independent predictors of cognitive performance (adjusted R² = 0.42, p < 0.001). Conclusions MRI-based volumetric reductions in the hippocampus and entorhinal cortex are significantly correlated with cognitive decline in MCI patients, suggesting their potential as predictive biomarkers for disease progression. Recommendations Recommend integrating MRI-based hippocampal and entorhinal cortex volumetry into routine MCI assessments for early detection and intervention.